Snf1-related kinase improves cardiac mitochondrial efficiency and decreases mitochondrial uncoupling - Rines, Amy K. (Nat Commun, 2017)
Ischaemic heart disease limits oxygen and metabolic substrate availability to the heart, resulting in tissue death. Here, we demonstrate that the AMP-activated protein kinase (AMPK)-related protein Snf1-related kinase (SNRK) decreases cardiac metabolic substrate usage and mitochondrial uncoupling, and protects against ischaemia/reperfusion. Hearts from transgenic mice overexpressing SNRK have decreased glucose and palmitate metabolism and oxygen consumption, but maintained power and function. They also exhibit decreased uncoupling protein 3 (UCP3) and mitochondrial uncoupling. Conversely, Snrk knockout mouse hearts have increased glucose and palmitate oxidation and UCP3. SNRK knockdown in cardiac cells decreases mitochondrial efficiency, which is abolished with UCP3 knockdown. We show that Tribbles homologue 3 (Trib3) binds to SNRK, and downregulates UCP3 through PPARα. Finally, SNRK is increased in cardiomyopathy patients, and SNRK reduces infarct size after ischaemia/reperfusion. SNRK also decreases cardiac cell death in a UCP3-dependent manner. Our results suggest that SNRK improves cardiac mitochondrial efficiency and ischaemic protection.